Pengaruh Rasio Keuangan Terhadap Pertumbuhan Laba Pada Perusahaan Farmasi Yang Terdaftar di Perusahaan BEI Tahun 2017-2023 - Sari, Diana Indah; Wafa, Zaenal (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
Financial statements are essential for assessing the financial health and performance of a company, serving as a key tool for management to provide relevant and accurate business information to stakeholders. The main component of financial statements is the company's profit, which plays an important role in evaluating management's performance in asset management and operations. This information is critical for internal and external parties, such as shareholders, creditors, and investors, who rely on earnings data for decision-making and strategy development. Earnings are generally recorded as the difference between revenues and expenses, with net income and earnings per share as commonly used measures. Accurate and consistent earnings reporting, supported by transparent accounting standards, is fundamental to informed decision-making. This study explores the impact of financial ratios on earnings growth in pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2023. The pharmaceutical sector, with its unique characteristics and challenges, such as dependence on research and development (R&D) and government regulations, exhibits different dynamics compared to other industries. Previous research has mostly focused on the manufacturing and services sectors, with limited research on the pharmaceutical sector. This study aims to fill this gap by examining the relationship between financial ratios, such as Return on Assets (ROA), Return on Equity (ROE), and Gross Profit Margin (GPM), to earnings growth in the pharmaceutical sector.